Four new Tapinomorphus Hartmann species from Angola, Zambia and Zimbabwe (Coleoptera: Curculionidae: Entiminae: Sciaphilini) - Borovec, Roman; Nakládal, Oto (Zootaxa, 2020)
Four new Tapinomorphus species are described and illustrated: Tapinomorphus angolanus sp. nov. from Angola, T. kudrnai sp. nov. from Zambia, T. latipennis sp. nov. and T. verunkae sp. nov. from Zimbabwe. This brings the total number of species in the genus to 20. Habitus images and illustrations of important characters are provided.